O papel do Receptor Ativado por Protease (PAR)2 na resposta efetora de macrófagos murinos estimulados com LPS - Ayslan Barra (2021)
The macrophage effector response begins with the recognition of pathogen-associated molecular patterns (PAMP) by pattern recognition receptors expressed on macrophages. The Toll-like receptor (TLR) 4 is an example of PAMP whose ligand is the lipopolysaccharide (LPS), a molecule derived from gram-negative bacteria capable of triggering a potent antimicrobial and pro-inflammatory response in macrophages. On the other hand, during tissue injury or infection, proteases generated by cells and / or secreted by microorganisms contribute to amplify the inflammatory response. The main mechanism occurs through receptors coupled to protein G called Protease Activated Receptors (PAR) that perform functions related to coagulation, cancer, pain, inflammation, among others. PAR2 is the most expressed subtype in macrophages and although this receptor functions as an innate sensor, little is known about its participation in the effector functions in macrophages. Thus, the objective of this work was to investigate the role of PAR2 in the effector responses of macrophages induced by LPS. For this, macrophages obtained from the peritoneal cavity of C57BL / 6 mice were stimulated with the synthetic agonist of PAR2 (SLIGRL-NH2, 30μM), LPS (100ng / mL) or both, and their phagocytic activity, nitric oxide production (NO), reactive oxygen species (EROS) and cytokines TNF, IL-1β, MCP-1, IL-6 and IL-10 were evaluated. We also evaluated the expression of PAR2, TLR4 and the inducible nitric oxide enzyme (iNOS), the physical interaction between PAR2 and TLR4, the signaling pathways involved in this phenomenon, the calcium-dependent mechanisms involved and the contribution of endogenous proteases and a PAR2 fragment, obtained after cleavage of its extracellular portion, on the pro-inflammatory effects of peritoneal macrophages stimulated with LPS. In some experiments, macrophages were pre-incubated with protein synthesis inhibitor (cyclohexemide, 20μg / mL) or gene transcription inhibitor (actinomycin D, 5μg / mL) before SLIGRL-NH2, LPS or both and before expression evaluation of PAR2 and TLR4. The coactivation of PAR2 and TLR4 enhanced macrophage effector functions such as phagocytosis, NO production, iNOS expression, EROS and pro-inflammatory cytokines. In addition, activation of PAR2 and / or TLR4 increased the expression of both receptors, this mechanism being dependent on gene transcription and de novo synthesis of these receptors, and the coincubation with the PAR2 and LPS agonist significantly increased colocalization and physical interaction between PAR2 and TLR4, confirming a cooperation between these receptors in the effector functions of macrophages. Pretreatment with protease inhibitor cocktail reduced LPS-induced calcium release, suggesting that possible proteases released by macrophages could autocrinically promote the activation of PAR2, while the PAR2 fragment did not change intracellular calcium levels, confirming that the PAR2-TLR4 synergism depends on the production of an active fragment. At last, we demonstrate that the mechanisms involved in enhancing the activation repertoire of macrophages mediated by PAR2-TLR4, are dependent on the transcription factor NFκB pathway and on the prolongation of the intracellular calcium release time, without, however, interfering with phosphorylation of via MAP kinase p38. In conclusion, this work demonstrates that PAR2 and TLR4 play an important role to enhance the effector functions of macrophages, providing further evidence for understanding the functioning of these cells in an infectious or inflammatory microenvironment in which proteases are present.